Meet the Expert : Titus Winters on Software Engineering Principles at Google - Winters, Titus (O'Reilly Media, Incorporated, 2020)
Google arguably maintains one of the largest codebases ever, and the expected lifespan of the codebase is at least another couple of decades. It's no surprise then that the company has learned many lessons related to the sustainability of software as it's figured out how to operate at a scale previously unattempted for a timespan longer than most others have considered. Learning from the difficulties that they encountered while wrangling with this unprecedented problem, Google's software engineers have tailored their practices to factor in time, scaling, and evidence-based decision making. In this Meet the Expert with Titus Winters, learn the practices, policies, and decisions Google has implemented to support robust and reliable code. You'll explore the themes of time and scale in the context of sustainable software engineering-and discover the impact (and trade-offs) that each of these factors has on the process of software development and maintenance. You'll also see how Google has shaped its engineering practices to take these principles into account. Recorded on August 3, 2020. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.